SERUM TRANSFERRIN RECEPTOR, SERUM FERRITIN AND SERUM TRANSFERRIN RECEPTOR-FERRITIN INDEX IN ADULTS WITH IRON DEFICIENCY ANAEMIA - Nadeem, Seema; Shah, Shahida; Iqbal, Touqueer; Iqbal, Zafar; Hanif, Ejaz (Journal of Ayub Medical College Abbottabad, 2011)
Background: Serum Ferritin (SF) and iron both show acute phase responses to inflammation, so iron may fall and ferritin rise independent of the marrow iron store. Bone marrow iron store has been considered the gold standard, but is invasive, painful and expensive and not suitable for everyone. Serum transferrin receptor (sTfR) which is the concentration of the soluble fragment of transferrin receptor in serum, is an important new haematological parameter. The ratio of sTfR to log SF is known as sTfR-SF index. This study was conducted to evaluate sTfR, Ferritin and sTfR-F Index in diagnosing and differentiating iron deficiency anaemia (IDA) from anaemia of chronic disease (ACD). Methods: One hundred and sixteen (116) adult subjects (80 anaemic and 36 controls) who already had their bone marrow examination done for various reasons were included in the study. sTfR, SF, and their index were measured and compared with bone marrow iron stores. Absence of iron stores denoted IDA whereas increased macrophage iron with decreased siderocytes and sideroblasts was diagnostic of ACD. Results: Out of 80 anaemic patients, 47 were diagnosed as IDA while 33 were diagnosed as ACD. In case of IDA the diagnostic accuracy of index was 91.57%, sTfR had accuracy of 85.54% while SF had accuracy of 75.90%. In case of ACD, the diagnostic accuracy of sTfR was 91.30%, index 89.86%, while SF had accuracy of 79.71%. Conclusion: sTfR-SF index is a better parameter than sTfR or ferritin alone but should only be used when the results of these parameters seem altered or a bone marrow aspiration is mandatory for diagnosis of ACD. The estimation of sTfR or index may offer a simple non invasive method that may enable more accurate assessments of iron status in such patients. Keywords: Serum Transferrin Receptor, Index, Iron deficiency anaemia